The count of Monte Cristo - Birnbaum, Roger; Reynolds, Kevin ([Burbank, CA] : Touchstone Pictures, 2002)
An innocent man, Edmond Dantes, is imprisoned for years on a godforsaken island while the friend who betrayed him takes Dantes ravishing fiancé for himself. Dantes eventually escapes, recovers a fortune in buried pirate treasure, transforms himself into the mysterious Count of Monte Cristo, and methodically goes about exacting his revenge
Executive producer, Chris Brigham ; editor, Stephen Semel ; screenplay, Jay Wolpert
Cast: Jim Caviezel, Guy Pearce, Richard Harris
VCD format
Keywords: Violence in motion pictures; Epic films